2007
DOI: 10.1111/j.1365-3016.2007.00845.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal smoking, social class and outcomes of pregnancy

Abstract: Exposure to tobacco during pregnancy is an important risk factor for infant health. Recently the prevalence of smoking during pregnancy has declined in our area. The objective of this study was to analyse the association between several social variables and the fetal exposure to smoking, as well as the association between maternal smoking and some adverse gestational outcomes. Data collection was cross-sectional. The study population were women in the city of Barcelona (Catalonia, Spain) delivering a child wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
4
10

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 30 publications
5
54
4
10
Order By: Relevance
“…Nicotine-addicted mothers tended to be younger and of lower educational level than non-smokers. These results coincide with those of Villalbí et al (2007). According to these authors, fewer women with higher educational levels and from families with non-manual jobs smoked, as was also the case with immigrants, those planning their pregnancy, and women whose partners did not smoke.…”
Section: Discussionsupporting
confidence: 77%
“…Nicotine-addicted mothers tended to be younger and of lower educational level than non-smokers. These results coincide with those of Villalbí et al (2007). According to these authors, fewer women with higher educational levels and from families with non-manual jobs smoked, as was also the case with immigrants, those planning their pregnancy, and women whose partners did not smoke.…”
Section: Discussionsupporting
confidence: 77%
“…11,18 The smoking pattern demonstrated in this study confirms previous research findings that smoking is more prevalent among relatively young women and among women who live in poor socioeconomic circumstances. 11,12,15,22 This may be explained by the marketing campaigns that are designed specifically to target young women. 25 In this study, it was found that women for whom primary school was their highest education level had around twice as much risk of smoking during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The social structure of smoking behavior during pregnancy is largely determined by social factors. [13][14][15] The consequences of pregnancy in situations of low socioeconomic level are determined through internal factors and the habit of cigarette smoking is among these factors. 16 Up to half of the adverse consequences of pregnancy are caused by smoking behavior among women living under low socioeconomic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Yapılan çalışmalarda gebelikte sigara kullanımı oranı %9-25 olarak gösterilmiştir. 13,14 Amerika Birleşik Devletleri Halk Sağlığı Servisine göre Amerika Birleşik Devletlerinde kadınların en az %11 i gebeliklerinde sigara içmektedir. 15 Anders ve Day, 2000 yılındaki yayınlarında gebelikte kadınların %15-20 sinin sigara içtiğini bildirmişlerdir.…”
Section: Oae Tarama Testi Yaklaşık Olarak 4-8 Dakika Sürdü Bebekleriunclassified